Analisis Kelayakan Finansial Usahatani Tebu di Desa Pasirbungur Kecamatan Purwadadi Kabupaten Subang - Fatah, Adrian Maulana; Abubakar, Abubakar; Fikri, Muhamad Rom Ali (Jurnal Ilmiah Wahana Pendidikan, 2024)
Pasirbungur Village is a village with a dominant area with sugarcane plantations and the land area reaches 1,744.0588 ha. The number of sugarcane farmers in Pasirbungur Village is not much because at the beginning of planting sugarcane farmers often experience losses. The purpose of this study is 1) to analyze the costs, revenues, income and profits of sugarcane farming in Pasirbungur Village, Purwadadi District, Subang Regency, 2) To analyze the feasibility of sugarcane farming in Pasirbungur Village, Purwadadi District, Subang Regency. This research is a quantitative research. Research data in the form of primary data and secondary data. Primary data were obtained from field observations and interviews with 33 respondents using questionnaires. Secondary data are obtained from BPS, books, journals, and articles. The data analyzed are total cost, revenue, revenue, profit, R/C ratio and BEP. The results of this study are known to average production costs of Rp. 81,851,402 / harvest then the average revenue is Rp. 102,254,545.45 / harvest, so that the average income is Rp. 44,635,909.09 / harvest, while the average profit is Rp. 20,403,143.93 / harvest with an average land area of 2,818 ha. The R/C ratio is 1.25 > 1 and to achieve minimum production BEP farmers must sell 693.92 quintals with a BEP Price of Rp. 64,037.46 / quintal and produce BEP Revenue of Rp. 55,513,831.81. This means that if sugarcane farmers in the research area produce sugarcane production of 693.92 quintals with a selling price of Rp. 64,037.46 / quintal, it will produce BEP revenue of Rp. 55,513,831.81. So that sugarcane farming has more value than the break-even point, which is to get a profit and is worth cultivating.